A social and cultural context to read children's drawing processes (Palíndromo, 2024)
This article is part of a doctoral research process in the area of analysis and interpretation of children's drawing processes and behaviors. The objective of the text is to study and propose some questions regarding the sociocultural and psychosocial dimensions of these processes in preschool boys and girls, in conversation with the biological, anthropological and physical dimensions that appear most often in children's first drawings. We intend to contribute to children's reading and understanding of graphic language. Our methodology is inserted in artistic and image-based research, since it aims to establish the relationship between multiple theories and studies (state of the art) and our collections of photographic and videographic material that collect direct observations of children's drawing processes (in a broad sense). As a result, we created our own analysis questions and categories and then applied them to the processes and their transcription. Provisionally, it seems to us that young children are permeable to the sociocultural context in the close and immediate environment of direct social interactions during the processes, while older children reflect in their drawings the culture and society of which they are part and in which they have grown up and been educated. Furthermore, it is important to point out that this approach to children's drawing leads us directly to the study of drawing as behavior, as a language and knowledge that is deeply human and embedded in both culture and the biophysical nature of the world.
Keywords: children's drawing; graphic language; sociocultural interaction; context; community; art education